2005
DOI: 10.1021/cm0483700
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Electrochromic Behavior of Novel Poly(aniline-co-4,4‘-diaminodiphenyl Sulfone)

Abstract: Electroactive conducting copolymers of aniline and 4,4‘-diaminodiphenyl sulfone (DDS) were prepared electrochemically. The cyclic voltammetric studies were carried out with different feed concentration of DDS on a glassy carbon electrode surface. The voltammograms exhibited different behavior for different concentrations of DDS. The effect of scan rate and pH on the electroactive copolymer film was studied. The copolymer showed good adherence on the glassy carbon electrode surface and gave a response up to pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Dan et al synthesized and characterized conducting poly(aniline-codiaminodiphenylsulfone) and showed that the reactivity of 4,4 -diaminodiphenylsulfone was greater than that of aniline [25]. Electrochemically synthesized copolymer of aniline and 4,4 -diaminodiphenyl sulphone by us exhibited novel electrochromic properties [26]. In this paper, the chemical copolymerization of aniline (ANI) with 4,4 -diaminodiphenyl sulphone (DDS) is presented.…”
Section: Introductionmentioning
confidence: 95%
“…Dan et al synthesized and characterized conducting poly(aniline-codiaminodiphenylsulfone) and showed that the reactivity of 4,4 -diaminodiphenylsulfone was greater than that of aniline [25]. Electrochemically synthesized copolymer of aniline and 4,4 -diaminodiphenyl sulphone by us exhibited novel electrochromic properties [26]. In this paper, the chemical copolymerization of aniline (ANI) with 4,4 -diaminodiphenyl sulphone (DDS) is presented.…”
Section: Introductionmentioning
confidence: 95%
“…The modified electrodes of poly(ANI-co-DDS), PEDOT, PEDOT/SDS, PEDOT/CTAB, poly(EDOT-co-DCF), poly (EDOT-co-DCF)/SDS, and poly(EDOT-co-DCF)/CTAB were prepared electrochemically on glassy carbon electrode as reported by us earlier [37][38][39].…”
Section: Fabrication Of Modified Electrodesmentioning
confidence: 99%
“…Studies have indicated that surface coated polymer films exhibit enhanced analytical response for the quantification of various biological and clinical analytes. The thickness, permeation and charge transport characteristics of the polymeric films can be controlled by the potential and current applied [2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Research on surface modified electrode has involved studies of the electrochemistry of the attached molecules, the catalysis and inhibition of various electrochemical processes and specific applications to such widely varying areas as photoelectrodes and analytical determinations [16,17].…”
Section: Introductionmentioning
confidence: 99%